Cendawan Tular Tanah (Rhizoctonia solani) Penyebab Penyakit Busuk Pelepah pada Tanaman Jagung dan Sorgum dengan Komponen Pengendaliannya - Soenartiningsih, Soenartiningsih; Akil, M.; Andayani, N. N. (Puslitbang Tanaman Pangan, 2015)
Sheath blight is an important disease of maize and sorghum. Yield decrease on susceptible varieties of both commodities due to the disease is high. The fungus survives in the form of sclerotia or hyphae in the soil or remains on infected plants. The pathogen has a wide range of host plants including members of the families Leguminosae, Solanaceae, Cucurbitaceae, and Gramineae, hence causes the fungi difficult to control. Control of the disease could be done biologically using antagoistic microorganisms such as Trichoderma spp., Gliocladium spp., and vesicular arbuscular mycorrhizae, planting resistant varieties, as well as mechanically, physically, and chemically.